Meninjau Kasus Intoleransi Beragama dan Gerakan Fundamentalisme Islam Indonesia dari Perspektif Moral Johann Gotlieb Fichte - Wolor, Pius Toli; Suban, Rikardus paulus; Teluma, Mario Laurentius C. B. (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
Religious intolerance cases in Indonesia still occur frequently. This happens due to the minimal awareness of the society. Additionally, it is also caused by the ideology and influence of Islamic fundamentalist groups. Therefore, the author utilizes the thoughts of Johann Gotlieb Fichte to shape societal awareness and highlight the errors of Islamic fundamentalists. The author employs a qualitative-descriptive method, elaborating research findings in descriptive form with sources from qualitative data. Consequently, data collection is conducted through literature review. The author presents five aspects from the research findings. Firstly, the awareness of individuals to use their reason in practicing religion. Secondly, everyone needs to ensure the religious freedom of others due to moral demands. Thirdly, there is a need for encouragement that upholds equality rights. Fourthly, individuals practicing religion need to prioritize morality to achieve common goals. Fifthly, there is a necessity for a language of diversity to be collectively embraced.